Afterlife beliefs and dream encounters with the dead among adherents of alternative spiritualities in Bosnia and Herzegovina - Ivnik, Tina (Studia mythologica Slavica, 2025)
This article examines the connection between the ideas adherents of alternative spiritualities in Bosnia and Herzegovina have about the afterlife and their understanding of dreams involving the dead. It explores how these ideas and interpretations are connected to the perceived agency of the dead, as experienced by my interlocutors in their dreams. Focusing on ideas about the afterlife within alternative spirituality, the article discusses why these beliefs have regained significance and how they have been reinterpreted in relation to modern/secular and religious explanations. By analysing the beliefs of individuals engaged in alternative spiritualities regarding the afterlife, it explores how these ideas shape their understanding of dreams featuring personally known deceased individuals. As beliefs about the afterlife influence how individuals perceive the state of the dead, it examines how these beliefs enable the dead to have agency upon the interlocutors in their dreams. The findings are based on ethnographic research conducted with spiritual individuals in Sarajevo and Banja Luka in Bosnia and Herzegovina.
Keywords: alternativna duhovnost; Banjaluka; Bosna in Hercegovina; folkloristika; izkušnja bližine smrti; ljudska verovanja; mrtvi; posmrtno življenje; sanje; Sarajevo; sodobna duhovna gibanja; spiritualizem